Compassione e linguaggio nelle riflessioni di Montaigne sugli animali (Itinera, 2012)
The study presents Montaigne’s considerations about the status of non-human animals. In his Essais the French philosopher describes compassion as the capability to pay attention to the claims for justice of weaker beings, showing how cruelty derives from the refusal or from the incapacity to listen to the voice of the “Other”; Montaigne’s fundamental thesis, according to which language is the most important vehicle of any correct ethical relationship, is thus confirmed. Empathy is not a “classical” virtue, grounded on fortitude, but rises, instead, from a weakness, which acquires a positive value inasmuch as it poses us on the same level of all other creatures. It has the quality of being grounded on the personal experience of the negativity of pain, which we share with all living beings, and is therefore incontrovertible.